Middle East region: Turkey - Erol Barkana, Duygun; Uzun, Ismail; Tarakçi, Devrim; Tarakçi, Ela; Betul Oktay, Ayse Betül; Akgül, Yusuf Sinan (Elsevier, 2023)
This chapter will first present health statistics for Turkey and describe conventional rehabilitation therapies used to rehabilitate patients with stroke. Next, we will present existing neurorehabilitation robotic centers that treat patients in Turkey and provide information about the upper/lower-extremity robots used in these centers. We will discuss the advantages and shortcomings of these robots and technological advances in neurorehabilitation. Then, we will describe the prototype upper/lower-extremity robots that are not yet used in the clinic but are still being developed in the universities to treat patients in Turkey. Next, we will discuss barriers to effective rehabilitation robotics and give an overview of the policies and legal and ethical issues around rehabilitation robotics in Turkey. Lastly, we will evaluate how rehabilitation has changed or is still changing during the COVID-19 pandemic, whether the need for rehabilitation robots will increase, and our opinions about the future of neurorehabilitation and what can be done further to use rehabilitation robots. © 2023 Elsevier B.V., All rights reserved.
Keywords: COVID-19 and rehabilitation; Rehabilitation robots; rehabilitation technologies in Turkey; technological rehabilitation; telerehabilitation